201TI Reinjection Predicts Improvement of Left Ventricular Function following Revascularization - Bartenstein, P.; Häsfeld, M.; Schober, O.; Matheja, P.; Schäfers, M.; Budde, Th.; Hammel, D.; Scheid, H.; Breithardt, G. (Nuklearmedizin - NuclearMedicine, 1993)
The aim of this study was to evaluate the correlation between improved TI uptake in reinjection imaging with improvements in regional wall motion and global ejection fraction following PTCA or aorto-coronary bypass surgery. 19 patients with CHD were investigated and divided into two groups according to their thallium uptake in the reinjection studies. Group I showed additional uptake on reinjection imaging compared to the redistribution image, whereas group II showed no additonal uptake. Both groups had a similar number and distribution of affected vessels and location of the leading stenosis. Stress, redistribution and reinjection images were obtained prior to revascularization and evaluated semiquantitatively from a bulls eye scheme. There was a postoperative increase in regional wall motion in group I from 5.3 to 8.8% whereas group II did not show a relevant change (6.3 vs 6.0%). The ejection fraction increased from 55.0 to 66.7% in group I and dit not increase in group II (59.8 vs 58.7%). The overall predictive value of the reinjection image for improvement in wall motion (> 10%) was 91 % and for the redistribution image 58%. Increased uptake in reinjection imaging predicts improved ventricular function following revascularization and indeed indicates viable myocardium with reversible functional impairment.Ziel der Studie war es, zu überprüfen, ob eine zusätzliche TI-Aufnahme in der Reinjektionsstudie mit einer Verbesserung der regionalen Wandbewegung und der globalen Auswurffraktion nach erfolgreicher Revaskularisierung korreliert. Insgesamt wurden 19 Patienten mit KHK vor und 3-6 Monate nach PTCA oder aorto-koronarem Bypass untersucht. Gruppe I zeigte gegenüber der Redistributionsstudie eine zusätzliche TI-Aufnahme in der Reinjektionsstudie, Gruppe II keine zusätzliche Anreicherung. Beide Gruppen waren hinsichtlich der Zahl und Verteilung der betroffenen Gefäße, der Lokalisation der führenden Stenose sowie der initialen Ejektionsfraktion vergleichbar. Postoperativ verbesserte sich die regionale Wandbewegung in Gruppe I von 5,3 auf 8,8%; Gruppe II zeigte keine signifikante Änderung. Die Auswurffraktion der Gruppe I stieg von 55,0 auf 66,7%; Gruppe II zeigte hier ebenfalls keine Änderung. Der positive Vorhersagewert im Gesamtkollektiv für eine Verbesserung der regionalen Wandbewegung (> 10%) betrug für die Reinjektionsstudie 91% und für die Redistributionsstudie 58%. Eine Verbesserung der Thalliumaufnahme in der Reinjektionsstudie läßt eine Verbesserung der Ventrikelfunktion nach Revaskularisierung erwarten. Mit Hilfe der Reinjektion kann somit Myokard mit reversibler Funktionseinbuße dargestellt werden.
Keywords: 201TI; reinjection; regional wall motion; revascularization